2019
DOI: 10.1002/smll.201805296
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Stretchable Rechargeable Devices with Organic Polymer Nanosheets Conformable to Skin Surface

Abstract: are too thick (>1 mm) to attach skin surface intimately. [18][19][20] Emerging micro norder printing techniques of electrode active materials enabled the fabrication of submillimeterthick batteries. [21] However, the intrinsic brittleness of the conventional inorganic electrodeactive materials and "harsh" electrolytes (e.g., flammable and toxic organic solvents for LIBs and alka line for Nihydrogen, zinc-air, and NiCd batteries) should be problematic for safety. The sealing must also be sufficiently thick and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…The porosity was significantly lower than those of the previously reported flexible electrodes with a porosity of >80% . The very low porosity yet flexible PTVE/LiCoO 2 /SWNT1 hybrid could be attributed to the highly adhesive and elastic properties of the radical polymer PTVE binder …”
Section: Properties Of the Flexible Cathodesmentioning
confidence: 61%
“…The porosity was significantly lower than those of the previously reported flexible electrodes with a porosity of >80% . The very low porosity yet flexible PTVE/LiCoO 2 /SWNT1 hybrid could be attributed to the highly adhesive and elastic properties of the radical polymer PTVE binder …”
Section: Properties Of the Flexible Cathodesmentioning
confidence: 61%
“…Because the polyethers were not mechanically tough enough to be used as self‐standing films, singe‐walled carbon nanotubes (SWNTs) or cellulose nanofibers (CNFs) were composited with the polymers as reinforcements (Figure S2 in the Supporting Information). We have reported hybrid nanosheets composed of a radical polymer and SWNTs as ultrathin electrodes (100 nm) . In the nanosheets, the polymers facilely filled the empty spaces of the SWNT networks, which were mechanically strong and electrically conducting .…”
Section: Resultsmentioning
confidence: 99%
“…We have reported hybrid nanosheets composed of a radical polymer and SWNTs as ultrathin electrodes (100 nm) . In the nanosheets, the polymers facilely filled the empty spaces of the SWNT networks, which were mechanically strong and electrically conducting . An only 1 μm‐thick rechargeable device was made from the nanosheet electrodes and brine as electrolyte solution .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While many groups concentrate on developing ultrathin and flexible skin‐laminatable devices, the issue of ultrathin power sources has attracted significantly less attention. To this end, Nishide et al from Waseda University in Tokyo, Japan, have demonstrated such ultrathin and stretchable redox‐active polymer/carbon nanotube rechargeable batteries . With SBS (poly(styrene–butadiene–styrene)) used as top and bottom encapsulation layers, the device structure of PTAm (poly(TEMPO‐substituted acrylamide); cathode)/PLA (poly(d,l‐lactic acid); separator)/PAQE (poly(anthraquinone substituted ethyleneimine); anode) devices with a total thickness of approximately 1 µm were shown undergoing physical stretching.…”
Section: Other Super‐ and Ultrathin Electronicsmentioning
confidence: 99%